Contemporary encounters in gender and religion: European perspectives - Gemzöe, Lena; Keinänen, Marja-Liisa; Maddrell, Avril (Palgrave Macmillan, 2016)
The fields of gender and religious studies have often been criticized for neglecting to engage with one another, and this volume responds to this dearth of interaction by placing the fields in an intimate dialogue. Taking a multi-disciplinary approach and drawing on feminist scholarship, the book undertakes theoretical and empirical explorations of relational and co-constitutive encounters of gender and religion. Through varied perspectives, the chapters address three interrelated themes: religion as practice, the relationship between religious practice and religion as prescribed by formal religious institutions, and the feminization of religion in Europe.